Metahemoglobinemia inducida por dapsona: reporte de un caso en el servicio de urgencia - Carroza N., Ignacio; Legua V., Camila (Revista Hospital Clínico Universidad de Chile, 2024)
Methemoglobinemia is a low prevalence but potentially severe condition in the Emergency Department. One of its leading causes is drug induction, dapsone being one of them. Dapsone is a synthetic sulfone with antimicrobial properties, often prescribed for prophylaxis against Pneumocystis jiroveci infection and other implications. This report presents the case of a 39-year-old male recently diagnosed with HIV on antiretroviral therapy along with prophylactic dapsone, who sought medical attention in the emergency room due to symptoms of cough, dyspnea, and fever. On admission, the patient exhibited a state of tachypnea and an oxygen saturation of 78% in room air, which is partially corrected with supplemental oxygen at an inspired oxygen fraction of 50%, achieving oxygen saturation of 90% by pulse oximetry. Chest X-ray revealed no abnormalities, and arterial blood gas analysis showed a partial pressure of oxygen of 380 mmHg with oxygen saturation of 100%. Given the disparity between pulse oximetry, arterial blood gas results, and the normal chest X-ray, a co-oximetry was conducted, revealing a methemoglobin level of 10.4% The patient was admitted to the ICU and continued receiving oxygen therapy. Dapsone was discontinued and the patient’s condition improved. without the need for methylene blue administration or alternative therapies.